Parametros energéticos de un horno continuo para la producción de cal a partir de la capacidad de producción - Castillo Gabriel, Angel Moisies (2017)
The purpose of the present study is to determine the energy parameters of a furnace for the production of lime from the production capacity. In order to carry out the experimental calcination tests of limestone, a vertical furnace with refractory lining with an anthracite combustion system and primary ignition was used by liquefied petroleum gas burner, in addition to an electric muffle furnace of 3kW, for the evaluation Limestone and lime as a product. An experimental tubular type vertical furnace was used for limestone firing tests, with internal refractory and carbon steel outer shell and anthracite coal in a stationary system. It was determined experimentally that 0.115 kg of carbon per kilogram of calcium oxide to be produced is required, 781.18 kcal is required for each kilogram of calcium oxide, with a thermal efficiency of 61.11%. In addition, 7.5 m³ of air was required for each kilogram of coal used.